A Rare Case of Gastrointestinal Stromal Tumor of the Abdominal Wall - Florin BOBIRCA; Dan DUMITRESCU; Lidia BELEGA-MURSOI; Anca BOBIRCA; Cristina ALEXANDRU; Horia DORAN; Traian PATRASCU (Modern Medicine)
Gastrointestinal stromal tumors (GIST) are rarely encountered in medical practice, developing with predilection in people over 40 years old. Their starting point is found in the digestive tract, and can appear anywhere along it. Normally, in the human body cells go through the processes of development, division and then apoptosis. In the case of gastro-intestinal stromal tumors, the cells divide continuously and the process of apoptosis is no longer carried out, forming these tumors, which can be benign or malignant. The essential medical treatment used in the case of gastrointestinal stromal tumors is Imatinib, which has the role of preventing the growth or even regression in size of the tumor in most cases. The specificity marker for GIST is represented by c-KIT protein, and immunohistochemically, the majority of gastrointestinal stromal tumors show positivity for CD34 and c-KIT. There are also extragastro-intestinal stromal tumors, for example located in the liver, duodenum, pancreas, but they are extremely rare, being considered rather as metastases from the primary tumor.